Messianic expectations in the Old Testament - W. Rose (In die Skriflig, 2001)
The New Testament is connected to the Old Testament in a number of different ways. It is not unusual to find the word “messianic” used to categorise all the different ways in which the writers of the New Testament find Christ (and, similarly, Jewish sources of the Second Temple Period later find the future Messiah) in the Old Testament, or to identify the specific passages in the Old Testament which are now seen to point to Christ/the Messiah. In this article I argue that, if one wants to be able to appreciate the diversity, one should abandon this indiscriminate use of the word “messianic”. After a brief discussion of the meaning and use of the Hebrew word xyvm in the Old Testament, I propose a definition of the phrase “messianic expectations” (expectations focusing on a future royal figure sent by God – someone who will bring salvation to God’s people and the world and establish a kingdom characterised by features such as peace and justice). Subsequently, the origin of these expectations is located as in the proclamation of the eighth-century prophets (Amos, Isaiah and Micah). Finally, one special category of messianic expectations, that is, messianic expectations in the Books of the Psalms, is dealt with.